Disrupted fornix integrity in children with chromosome 22q11.2 deletion syndrome. Issue 1 (30th April 2015) - Deng, Yi; Goodrich-Hunsaker, Naomi J.; Cabaral, Margarita; Amaral, David G.; Buonocore, Michael H.; Harvey, Danielle; Kalish, Kristopher; Carmichael, Owen T.; Schumann, Cynthia M.; Lee, Aaron; Dougherty, Robert F.; Perry, Lee M.; et al.
Abstract: The fornix is the primary subcortical output fiber system of the hippocampal formation. In children with 22q11.2 deletion syndrome (22q11.2DS), hippocampal volume reduction has been commonly reported, but few studies as yet have evaluated the integrity of the fornix. Therefore, we investigated the fornix of 45 school-aged children with 22q11.2DS and 38 matched typically developing (TD) children. Probabilistic diffusion tensor imaging (DTI) tractography was used to reconstruct the body of the fornix in each child׳s brain native space. Compared with children, significantly lower fractional anisotropy (FA) and higher radial diffusivity (RD) was observed bilaterally in the body of the fornix in children with 22q11.2DS. Irregularities were especially prominent in the posterior aspect of the fornix where it emerges from the hippocampus. Smaller volumes of the hippocampal formations were also found in the 22q11.2DS group. The reduced hippocampal volumes were correlated with lower fornix FA and higher fornix RD in the right hemisphere. Our findings provide neuroanatomical evidence of disrupted hippocampal connectivity in children with 22q11.2DS, which may help to further understand the biological basis of spatial impairments, affective regulation, and other factors related to the ultra-high risk for schizophrenia in this population. Highlights: Lower fractional anisotropy (FA) and higher radial diffusivity (RD) were observed bilaterally in the body of the fornix in children with 22q11.2 deletion syndrome (22q11.2DS). Smaller volumes of hippocampal formations were found in children with 22q11.2DS. Correlations between the reduced hippocampal volumes and the fornix lower FA and higher RD was demonstrated in the right hemisphere.